2000
DOI: 10.1007/bf03018995
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Hemodynamics, intra-mucosal pH and regulators of circulation during perioperative epidural analgesia

Abstract: Purpose: To evaluate the effects of perioperative epidural analgesia on hemodynamics, splanchnic perfusion and regulators of circulation.Methods: Twenty patients undergoing aortic surgery were randomised into two groups: epidural analgesia group (EAG): epidural analgesia with bupivacaine (15 ml, 0.125%) was started before surgery. Eight and 16 hr postoperatively 10 ml bupivacaine 0.125% and 1 mg morphine were given. Control group (COG): patients received no epidural catheter. Monitoring included pulmonary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…On the other hand, Piper et al . [18] reported significant difference in MAP before clamping and after release of clamp, with lower values in patients under combined general–epidural anesthesia. Finally, SVR was significantly lower in Group A at T3–T4 compared with T0, whereas in Group B SVR was significantly higher during clamping (T2) compared with T0, highlighting the beneficial effect of epidural anesthesia on sympathetic blockage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Piper et al . [18] reported significant difference in MAP before clamping and after release of clamp, with lower values in patients under combined general–epidural anesthesia. Finally, SVR was significantly lower in Group A at T3–T4 compared with T0, whereas in Group B SVR was significantly higher during clamping (T2) compared with T0, highlighting the beneficial effect of epidural anesthesia on sympathetic blockage.…”
Section: Discussionmentioning
confidence: 99%
“…Piper et al . [18] concluded that perioperatively administration of bupivacaine epidurally has no beneficial effects on hemodynamics or intestinal pH, but in this particular study local anesthetic was administered at bolus doses in constant time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that there is an increase in both coagulation activation and fibrinolysis but that there is some fundamental change in the balance between the two systems. 31,32 Patients who were taking oral contraceptive pills or hormone replacement therapy were instructed to discontinue use 1 week before surgery. It is interesting to note that this did not decrease the rate of venous thromboembolism in this group to a nonsignificant level.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…CO 2 -gap was also comparable between groups. 1 These findings are in disagreement with the majority of studies on the effects of epidural anesthesia on splanchnic perfusion during abdominal surgery. Most studies reported beneficial effects of epidural anesthesia, resulting in increased regional blood flow or gastric pHi.…”
Section: Epidural Anesthesia and Splanchnic Perfusionmentioning
confidence: 83%